Implementasi Soft Skill dan Hard Skill Dalam Pendidikan Islam - Yulianti, Evi; Saputra, Muklas Ade; Busral, Busral; Hakim, Lukman (Al-Ashri: Ilmu-Ilmu Keislaman, 2023)
Social competence is the teacher's ability to communicate and interact effectively and efficiently with students, fellow teachers, parents/guardians of students, and the surrounding community. Social competence interpersonal skills, namely the ability to build relationships with other people, effectively in the form of; communication skills, motivation skills, collaboration skills, and leadership skills. Hard skills are several skills possessed by a teacher whose concrete form can be captured through the senses or observed directly because the procedures are technical or administrative. This research uses the literature study method. Literature studies are carried out by reading library sources to obtain the necessary data. The data sources used come from secondary data, the data was collected through textbooks, scientific journals, periodicals, ebooks, websites, statutory regulations, and other sources relevant to the research problem. Hard skills are divided into two parts, namely; Pedagogical competency is the ability to manage student learning which includes understanding students; and Professional competency is the ability to master subject matter broadly and in depth. A professional educator in the Islamic view is an educator who has expertise. Development efforts in Islamic education can be done in several ways, namely taking part in teacher upgrading, taking part in teacher deliberations in the field of study, taking courses, increasing knowledge through mass or electronic media, and improving the profession through self-study.